Body Resistance and Productive Performances of Crossbred Local Chicken Fed Inulin of Dahlia Tubers - N Fajrih; N Suthama; V D Yunianto (Media Peternakan, 2014)
The research was aimed to examine the role of inulin as a prebiotic derived from dahlia flower tuber in the form of powder and extract as a prebiotic on body immunity of crossbred local chicken. The research was assigned in a completely randomized design with 7 treatments and 4 replications (10 birds each). The treatments applied were T0: basal ration, T1: ration + 0.4% powder, T2: ration + 0.8% powder, T3: ration + 1.2% powder, T4: ration + 0.39% extract, T5: ration + 0. 78% extract, T6: ration + 1.17% extract. The birds were reared for conditioning from day 1 until day 21, and dietary treatment was given thereafter until 11 wk of age. The data were statistically analyzed according to ANOVA and continued to Duncan test at the level of 5% probability. The results showed that feeding inulin in the form of powder or extract significantly (P